Media Smart Apps Creator: Pengembangan dan Validasi untuk Meningkatkan Pemahaman Konsep IPAS Di Sekolah Dasar - Amanah Mardika Megi Sya’adah; Ahmad Ipmawan Kharisma; Mochammad Miftachul Huda (Jurnal Tematik, 2025)
This study aims to determine the validity, practicality, and effectiveness of digital learning media based on Smart Apps Creator in improving the understanding of IPAS concepts among fifth-grade elementary school students. The type of research used is Research and Development (R&D) with the ADDIE model and a control group pretest-posttest design with fifth-grade students at Bedahan Public Elementary School as the subjects. Data collection techniques include validation, questionnaires, and concept understanding tests. There are two analysis techniques: prerequisite analysis testing and hypothesis testing. The validation results showed that the media fell into the highly valid category with scores from media experts of 3.88; design experts of 3.93; content experts of 3.79; and learning tools of 3.83. The media was also deemed highly practical based on student responses from small groups (3.35) and large groups (3.52), as well as student activities with scores of 3.45 and 3.75. The effectiveness of the media was proven through a paired t-test with a significance level of 0.026 < 0.05 and an N-Gain Score in the “moderate” category. Thus, the digital learning media based on Smart Apps Creator has been proven to be valid, practical, and effective in enhancing elementary school students' understanding of IPAS concepts.